Impact of corruption on selected indicators of environmental quality a cross country analysis. - Varon, Therese Claire D.; Yambing, Kessiah Marie M. (2015.)
Corruption has been an economic, political and social concern among countries . Although there have been growing number of studies on corruption, most of these studies are limited on the impact on corruption, most of these studies are limited on the impact of corruption on governance and institutional quality. Studies on the impact of corruption on environment quality has been rarely tackled hence the relationship between corruption and environmental qualtiy has not been clearly established. This study aims to provide information on the linkages of corruption and environmental quality through identifying the impact of corruption on selected environmental indicators of environmental quality using cross country data analysis and OLS estimation. Results show that corruption has a significant impact on some of the indicators of environmental quality such as the change in forest cover, carbon dioxide emission and fish stock overexploitation. On the other hand, corruption appears to have no effect on sulfur dioxide emission.
Research Paper (Undergraduate, Bachelor of Science in Economics. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Corruption; Yambing, Kessiah Marie M